The ontological demand: on the ethics of being-in-common in Jean-Luc Nancy and Achille Mbembe - Gerber, Schalk Hendrik (Stellenbosch : Stellenbosch University, 2023)
Thesis (DPhil)--Stellenbosch University, 2023.